CLINICAL CONSIDERATIONS REGARDING VARIATIONS IN ORIGIN OF THE SUPERIOR THYROID ARTERY - A SYSTEMATIC REVIEW - Victor Nimigean; Vanda Roxana Nimigean; Alexandru Poll; Valentin Daniel Sîrbu; Simona Andreea Moraru (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study: the superior thyroid artery (STA) is the main artery which vascularises the larynx and the thyroid gland. Being aware of the variations in origin of the STA can be useful during surgical procedures. The purpose of the study is to document in the specialised literature the origin of the STA at the level of the carotid triangle. Material and methods: an analysis of 92 summaries of scientific papers, 45 in extenso articles, using ISI Thomson Web of Knowledge, PubMed and MedLine databases, and, additionally, a search in 7 anatomy books were performed. Results: the variations in origin of STA were mostly observed unilaterally, less of them were found bilaterally, but many publications did not present observations regarding the unilateral or bilateral nature of these origins. By order of prevalence, there are three main types of STA origin: type I - origin from the external carotid artery, type II - origin from the bifurcation of the common carotid artery and type III - origin from the common carotid artery. Conclusions: the results depict a wide variety of origins of STA, which go against classic anatomical descriptions, offer a better perspective for surgeons and can contribute to the clinical success improvement of surgical procedures performed in the anterior region of the neck.